Study on the Antibacterial and Bactericidal Effects of Ailanthus altissima Leaves Extract - Huo, Qing; Shao, Jie; Lin, Qiang (Asian Journal of Chemistry, 2012)
In present studies, the antibacterial and bactericidal effection of the A. altissima leaves extract are reported. Three different concentrations of A. altissima leaves extract were tested for the activities of antibacterial and bactericidal on Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The inhibition zone diameter of the three bacteria was tested using the method of filter paper diffusion. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were tested by the double dilution method. Three different concentrations of A. altissima leaves extract all have antimicrobial effect. Therefore, the inhibitory effect is more evident at higher concentration of the drug. The same concentration of Ailanthus altissima leaves extract on different amounts of bacterial suspensions have inhibitory effect, the greater the amount of bacterial suspension, the bigger inhibition zone diameter, the inhibitory effect is more evident. The minimum inhibitory concentrations of A. altissima leaf extract against S. aureus, P. aeruginosa, E. coli were 35.0, 8.8 and 70.0 mg/mL, respectively. The inhibitory effect of P. aeruginosa is the strongest. The minimum bactericidal concentration of A. altissima leaf extract against S. aureus, P. aeruginosa, E. coli were 35.0, 17.5 and 70.0 mg/mL, respectively. Therefore, the bactericidal effect on P. aeruginosa is the strongest.